Seismic microzoning in Skopje, Macedonia. Issue 98 (July 2017) - Lee, V.W.; Trifunac, M.D.; Bulajić, B.D.; Manić, M.I.; Herak, D.; Herak, M.; Dimov, G.
Abstract: Seismic microzonation maps for Skopje (Macedonia) are presented based on the Uniform-Hazard-Spectrum (UHS) methodology. UHS satisfies the guidelines for performance-based design (PBD), which require specification of two sets of spectral amplitudes, one for which the structure will remain essentially linear, and the other for which it will undergo a nonlinear response. The UHS method also considers the contributions from large distant earthquakes and includes simultaneous effects of site geology and site soils. The maps presented include the effects of near and distant large earthquakes in a balanced way, spatial distribution of seismic activity, site geology, and site soil properties. Highlights: Microzonation maps, which include a description of site geology and site soil. Contribution of large distant earthquakes to long period design spectra. Mapping hazard for earthquakes with different attenuation laws. Application of Uniform Hazard Spectra method to seismic microzonation.